Studi Kasus: Kesinambungan Perawatan pada Ny. “N” dengan Kehamilan Resiko Rendah - fitri, fitri yuniarti; Purwandari, Eka Sri; Basuki, Revi Baswantari (STIKES dan AKZI Karya Husada Kediri, 2024)
Pregnancy and childbirth are normal, natural, and healthy processes. Pregnancy with Poedji Rochyati Score Card 2 is a low-risk pregnancy. Although low-risk, mothers must always be vigilant because every pregnancy is at risk of complications that can endanger the mother and fetus. The purpose of this case study is to provide midwifery care with Continuity of Care to Mrs.